Cyclooxygenase-2 and von Willebrand factor—an immunohistochemical study of the equine foot with and without laminitis, post-mortem perfused with paraffin oil - Underberg, Bianca A.; Van der Vekens, Elke; Drews, Barbara; Kaessmeyer, Sabine (Frontiers in Veterinary Science, 2025)
ObjectiveEquine laminitis is a complex and potentially fatal disease characterized by severe vascular and inflammatory alterations within the equine foot. This study aimed to develop immunohistochemistry (IHC) protocols for the detection of cyclooxygenase-2 (COX-2) and von Willebrand factor (vWF) in equine feet with and without laminitis, post-mortem perfused with paraffin oil.Materials and methodsA total of 12 equine forelimbs from 8 horses were utilized in this study, divided into two study cohorts: one with laminitis and the other as a non-laminitis control. To develop the IHC protocols thoroughly, the tissue samples were categorized into three groups: fresh, frozen-thawed, and frozen-thawed-perfused. IHC protocols for COX-2, a marker for inflammation, and vWF, a marker for vascular endothelial cells, were developed, respectively, optimized for use across these tissue groups. Samples from both study cohorts were processed and morphologically analyzed to assess tissue preservation and efficacy of immunostaining techniques.ResultsOnce the optimal paraffin embedding as well as combination of blocking reagents, blocking duration and antibodies had been empirically determined, COX-2 and vWF immunostaining were successful in all tissue groups. Reducing the embedding time in paraffin from 24 h to 2 h and positioning the samples at a 45° angle within the embedding cassette optimized the cutting results for microtome sectioning. Immunostaining specificity was good and results of COX-2 and vWF in both study cohorts were comparable and reliable between all three tissue groups. COX-2 was considerably elevated in the laminits cohort, predominantly in basal and parabasal cells, fibroblasts, and endothelial cells. vWF immunostaining effectively highlighted the vascular endothelial cells, revealing vascular compression and dilation, especially in the laminitis cohort.Conclusion/discussionThis study provides evidence that COX-2 and vWF can be reliably detected in equine lamellar hoof tissues, after undergoing freezing, thawing, and perfusion treatments. The established IHC protocols represent valuable diagnostic tools for studying the inflammatory and vascular changes associated with the equine foot. These methods can be applied to post-mortem cadaver models that have been frozen and perfused with paraffin oil, thus reducing the number of live animals required for research.